Development and piloting of a Community of Practice to support learning and improvement in health promotion practice within NSW local health districts - Courtney Barnes; Rachel Sutherland; Gavin Jones; Nina Kingon; NCOIS Research Collaborative; Luke Wolfenden (Sax Institute, 2023)
Objectives: Health Promotion Units within New South Wales (NSW) local health districts (LHDs) frequently collaborate and test innovations to address priority health issues or approaches to support the implementation of a health promotion program in a way that is consistent with the needs, resources, and contexts of their regions. Compatible with learning health system approaches, mechanisms to facilitate the exchange of evidence and expertise across districts could improve the collective impact of health promotion services across the state. This study aimed to assess the use of a health promotion Community of Practice (CoP) model as a strategy to achieve this. Type of program or service: This paper describes and shares experiences from the development and piloting process of a CoP model to develop, evaluate and exchange learnings to improve approaches to support the adoption of an effective healthy lunchbox program ('SWAP IT') across three LHDs. Results: The functioning of the CoP was supported by key activities, funding and infrastructure over a 2-year period, including: planning workshops, implementation check-ins, and knowledge exchange meetings. A particularly novel aspect of the CoP was the harmonised evaluation of different, locally developed strategies to facilitate program adoption across the three LHDs. The alignment of the CoP with local and state priorities, as well as the operation of the CoP in a way that did not impose significant time demands, was seen as important for the sustainability of the CoP. Lessons learnt: Findings from the piloting process suggest that a formalised CoP shows promise as an effective model to enhance health promotion collaboration, information sharing and practice across LHDs, which may be suitable for broader application across the state.